Ginseng, Hypothalamo-Pituitary-Adrenal Axis and Cortisol, a Short Pubmed Approach of their Relationship - Jurcău, Ramona-Niculina; Jurcău, Ioana-Marieta; Colceriu, Nicolae-Alexandru; Pîrvan, Răzvan-Titus; Kwak, Dong Hun (Didactica Danubiensis, 2023)
Introduction. Ginseng (G) is an Asian plant used as an adaptogen, that has the ability to normalize bodily functions compromised by stress. Hypothalamic-pituitary-adrenal axis (HPA) is the main effectors of the stress response and cortisol (C) is the most used marker of stress. Materials and method. In order to highlight the relationship between G and stress, the keywords selected for analysis were G+HPA and G+C. The time periods analyzed were from 1970 to 2021. The Pubmed filters selected were: Species and Sex. Results. For G+HPA: publications with An were the most numerous and had the greatest numerical rise; reserch dynamic for the sex filter had a lower increase in time. For G+C: publications with H were the most numerous and had the greatest numerical rise; dynamic researches with HF had the lowest increase in time. Conclusions. 1) The research on the combination of the keywords G+HPA and G+C falls under the theme of the relationship between G and stress. 2) Research on animals predominated, compared to those on human subjects. 3) Research with subjects from both genders was preferred. 4) The research related to Ginseng and HPA, respectively to Ginseng and Cortisol, although numerically reduced, proves a continuously growing interest of researchers for this subject.